Respuesta :

ANSWER:

value of "a" is: a= -b√3+7+4√3

value of "b" is:  [tex]\frac{-a\sqrt{3}+7\sqrt{3} }{y} +4[/tex]

STEP-BY-STEP EXPLANATION:

how to get the value of "a":

1. (rationalize the denominator)

(2 + √3) × (2 + √3) =a + b√3

2. (write the repeated multiplication in exponential form)

(2 + √3)² =a + b√3

3. (use (a + b)² = a² + 2ab + b²  to expand the expression)

4 + 4√3 + 3 = a + b√3

4. ( add the numbers)

7 + 4√3 = a + b√3

5. (move the variable to the left-hand side and change its sign. then, move the constants to the right-hand side and change their signs)

-a + 7 + 4√3 = b√3  ⇔ -a = b√3 -7 - 4√3

6. (change the signs on both sides of the equation)

a = -b√3 + 7 + 4√3

how to get the value of "b":

1. (rationalize the denominator. then, use the commutative property to reorder the terms)

(2 + [tex]\sqrt{3}[/tex]) × (2 + [tex]\sqrt{3}[/tex] ) = a + b[tex]\sqrt{3}[/tex]   →  (2 + [tex]\sqrt{3}[/tex]) × (2 +[tex]\sqrt{3}[/tex] ) = a + [tex]\sqrt{3}[/tex]b

2. (write the repeated multiplication in exponential form)

(2 + √3)² =a + [tex]\sqrt{3}[/tex]b

3. (use (a + b)² = a² + 2ab + b²  to expand the expression)

4 + 4[tex]\sqrt{3}[/tex] + 3 = a + [tex]\sqrt{3}[/tex]b

4. (add the numbers)

7 + 4 [tex]\sqrt{3}[/tex] = a + [tex]\sqrt{3}[/tex]b

5. (move the expression to the left-hand side and change its sign. then, move the constants to the right-hand side and change their signs)

- [tex]\sqrt{3}[/tex]b + 7  + 4 [tex]\sqrt{3}[/tex] = a  → -[tex]\sqrt{3}[/tex]b = a - 7 - 4[tex]\sqrt{3}[/tex]

6. (divide both sides of the equation by [tex]-\sqrt{3}[/tex])  

b = [tex]- \frac{a}{\sqrt{3} } + \frac{7}{\sqrt{3}} + 4[/tex]

7. (rationalize the denominator)

b = [tex]b=-\frac{a\sqrt{3} }{\s3}} +\frac{7\sqrt{3} }{{3} } +4[/tex]

8. (write all numerators above the common denominator)

b =  [tex]\frac{-a\sqrt{3}+7\sqrt{3} }{y} +4[/tex]

there you go! I hope this helped. goodluck! :)

ACCESS MORE